Teaching and discussing about risk: seven elements of potential significance for science education. Issue 9 (13th June 2019) - Schenk, Linda; Hamza, Karim M.; Enghag, Margareta; Lundegård, Iann; Arvanitis, Leena; Haglund, Karin; Wojcik, Andrzej
ABSTRACT: The present paper takes its point of departure in risk being a relevant content for science education, and that there are many different approaches to how to incorporate it. By reviewing the academic literature on the use and definitions of risk from fields such as engineering, linguistics and philosophy, we identified key elements of the risk concept relevant for science education. Risk is a phenomenon of the future that may be conveyed by our activity, it is something that may or may not take place. Hence, at the core of risk we find uncertainty and consequence. Furthermore, the elements of probability and severity are relevant modifiers of the consequence, as well as both subject to uncertainty. Additionally, in framing, understanding and decision-making on risk, as individuals or society, we need to acknowledge that risk has both objective and subjective components, lying in the interface between knowledge and values. In this paper, we describe how these key elements were derived from the literature and derive a schematic model of the risk concept for the purpose of science education. We further discuss how this model may assist in planning, execution and evaluation of teaching activities explicitly or implicitly involving risk issues.